ANALISIS FAKTOR PRODUKSI KOPI DI KECAMATAN PANTAI CERMIN KABUPATEN SOLOK - Fitri, Elva Rahmi; Erlinda, Rita; Sorel, Deni (Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Mataram, 2025)
This study aims to analyze the influence of production factors on coffee farm outputs in Pantai Cermin District, Solok Regency. The analytical method employed is a multiple linear regression approach. The independent variables analyzed include labor, land area, and fertilizer usage. The results show that labor has an elasticity of 0.606, indicating that a 1% increase in labor will increase production by 0.606%. Land area has an elasticity of 0.79, meaning a 1% increase in land area will result in approximately a 0.79% increase in production. Meanwhile, fertilizer has a very low elasticity of 0.013, suggesting that changes in fertilizer usage have an insignificant effect on coffee yield. The coefficient of determination (R²) of 0.85 indicates that 85% of the variation in coffee production can be explained jointly by these three variables. These findings suggest that increasing coffee production can be more effectively achieved by optimizing labor utilization and expanding cultivated land. This study provides valuable insights for farmers and stakeholders in formulating strategies to enhance the productivity and efficiency of coffee farming.